Expanding disciplinary and interdisciplinary core idea maps by students to promote perceived self-efficacy in learning science - Helen Semilarski; Regina Soobard; Jack Holbrook; Miia Rannikmäe (SpringerOpen, 2022)
Abstract Background The goal of this research was to determine students' perceived self-efficacy in science classes through involving students in expanding disciplinary core idea (DCI) and interdisciplinary core idea (ICI) maps, as a method to visualize knowledge (utilizing mind mapping and concept mapping) to support students to integrate interdisciplinary learning. The research involved (a) creating (by science educators) eight curriculum-related, disciplinary core idea maps and two interdisciplinary core idea maps; (b) teachers guiding students in an experimental group, to make interdisciplinary connections so as to expand DCI and ICI maps in an intervention lasting a year and a half from grade 10 to 11; (c) providing feedback on students' developed DCI and ICI maps; (d) administering questionnaires seeking students' perceptions about their self-efficacy towards core ideas, both before and after the intervention and (e) interviewing science teachers (5) and selected students (25), after the intervention, about their perceptions towards the use and outcomes of their DCI and ICI maps. Besides the experimental group, a control group (no intervention) was involved. Results Outcomes showed that the intervention (guiding students in creating disciplinary and interdisciplinary core idea maps to visualize their learning) supported students significantly in their perceived self-efficacy in the fields of Life Science and Earth Science, plus in the use of Models and Systems. In Physics and Chemistry, the students' perceived self-efficacy was not statistically significantly positive after the conducted intervention. This stemmed from disciplinary core ideas, related to Physics and Chemistry, being more abstract, with students making fewer connections and integrating less new knowledge into the related DCI and ICI maps. In the interviews, both teachers and students stated that the intervention (including expansion of DCI and ICI maps) supported students' science learning. Conclusions Creating and expanding disciplinary and interdisciplinary core ideas more clearly indicates students' learning, through their ability to make meaningful connections, enabling students to raise their self-efficacy in preparing for their future. The results from this research demonstrate that students' perceived self-efficacy can occur through knowledge visualization by expanding both DCI and ICI maps enabling the making of greater interdisciplinary connections.